Correlation Of Self-Efficacy In Differentiated Learning With Students’ Mathematical Communication Skills In Vocational School - Slamet Slamet; Quensy Riani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to determine the relationship between self-efficacy in differentiated learning and the mathematical communication skills of vocational school students. The research method employed is a quantitative approach utilizing correlational techniques. The research sample consisted of 36 vocational school students selected through random sampling. The instruments included a self-efficacy questionnaire with 29 statements and a descriptive test assessing mathematical communication skills with eight items. Data analysis techniques included normality tests, linearity tests, and Spearman correlation tests, as the data did not meet the assumptions of linearity. The results revealed a Spearman correlation coefficient value 0.995, with a significance (Sig. 2-tailed) of 0.000. This indicates a strong and significant relationship between self-efficacy and students' mathematical communication skills. This study emphasizes the importance of teachers' efforts in enhancing students' self-efficacy through differentiated learning to foster the optimal development of their mathematical communication skills.